2021
DOI: 10.1002/jcv2.12046
|View full text |Cite
|
Sign up to set email alerts
|

A drop‐in centre for treating mental health problems in children with chronic illness: Outcomes for parents and their relationship with child outcomes

Abstract: Background Children with chronic health conditions and their parents are at greater risk of developing emotional and behavioural problems compared to their physically healthy peers. The psychological impact on parents is crucial to understand given the relationship between parental mental health and child emotional and behavioural difficulties. This study was part of a broader research project examining the acceptability, feasibility and impact of a ‘Mental Health and Psychological Wellbeing Drop‐in Centre’ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 91 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Similarly, these studies should also consider the impact on the wider family unit and investigate the impact on parental and sibling outcomes. In the main study investigating the drop-in centre for children with long-term physical health conditions which offered low-intensity intervention presented in this study, we found that parental mental health also improved significantly after attending the centre for support for the child (Bennett et al ., 2021c). We must also consider the variation in presenting problems and genetic conditions in our sample when drawing conclusions from the study for wider commissioning of services.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, these studies should also consider the impact on the wider family unit and investigate the impact on parental and sibling outcomes. In the main study investigating the drop-in centre for children with long-term physical health conditions which offered low-intensity intervention presented in this study, we found that parental mental health also improved significantly after attending the centre for support for the child (Bennett et al ., 2021c). We must also consider the variation in presenting problems and genetic conditions in our sample when drawing conclusions from the study for wider commissioning of services.…”
Section: Discussionmentioning
confidence: 97%
“…A drop‐in centre in a paediatric hospital delivering brief cognitive behavioural interventions may be one way for more children to access evidence‐based treatments. This was the goal of the ‘Lucy project’: to evaluate the acceptability, feasibility and impact of a ‘Mental Health and Psychological Wellbeing Drop‐in Centre’ in a tertiary paediatric hospital setting (Catanzano et al, 2021 ) and the quantitative outcomes are reported elsewhere (Bennett et al, 2021 ; Catanzano, Bennett, Kerry, et al, 2020 ; Clarke et al, 2022 ). The project was an uncontrolled trial of young people, their siblings and carers attending a national paediatric hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Future research will be able to tell. Should this putative d factor be confirmed, it would have substantial implications not only from a theoretical or even philosophical standpoint, but also from a practical perspective, providing a strong rationale for the integrated care for children and adolescents advocated in this issue by Fazel et al (2021) and Bennett et al (2021).…”
mentioning
confidence: 99%
“…The studies published in the special issue contribute to further our understanding on the links between Attention-Deficit/Hyperactivity Disorder (ADHD) and asthma (Sun et al, 2021); the relationship between anorexia nervosa and inflammatory bowel diseases (Larsen et al, 2021); the association of retinal vascular calibre with regional brain structure in adolescent bipolar disorder (Mio et al, 2021); the role of integrated care for child and adolescent health (Fazel et al, 2021); the acceptability, feasibility and impact of a drop-in centre to address emotional and behavioural problems in children with chronic physical conditions (Bennett et al, 2021); the efficacy of group-based Acceptance and Commitment Therapy for adolescents with multiple functional somatic syndromes (Kallesøe et al, 2021); and the evidence on physical exercise interventions in child and adolescent mental health (Carney & Firth, 2021). These studies add to and complement, with more fine-grained information, an increasing body of empirical evidence on the relationships between mental disorders and physical conditions in children and adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation